2023
DOI: 10.3389/fvets.2023.1118302
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-oligosaccharides fed during gestation increase Rotavirus A specific antibodies in sow colostrum, modulate the microbiome, and reduce infectivity in neonatal piglets in a commercial farm setting

Abstract: IntroductionRotavirus A is a major cause of acute dehydrating diarrhea in neonatal pigs resulting in significant mortality, morbidity, reduced performance and economic loss. Commercially available prebiotic galacto-oligosaccharides are similar to those of mammalian milk and stimulate the development of the microbiota and immune system in neonates. Little is known about the effects of supplementing sows' diets with galacto-oligosaccharides during gestation. This study aimed to determine if dietary galacto-oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…These bacteria can enhance local immune responses within the intestinal mucosa and stimulate B lymphocytes to release IgA, inhibiting and killing pathogens [46]. Consistent with our results, Lee et al [48] found that GOS significantly increased the concentrations of IgA in sow colostrum during lactation and reduced the number of harmful bacteria in the faces of fed piglets. Moreover, Alizadeh et al [49] also demonstrated that GOS can increase secretory IgA levels in the saliva of piglets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These bacteria can enhance local immune responses within the intestinal mucosa and stimulate B lymphocytes to release IgA, inhibiting and killing pathogens [46]. Consistent with our results, Lee et al [48] found that GOS significantly increased the concentrations of IgA in sow colostrum during lactation and reduced the number of harmful bacteria in the faces of fed piglets. Moreover, Alizadeh et al [49] also demonstrated that GOS can increase secretory IgA levels in the saliva of piglets.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have also shown that supplemen-tation with GOS increases the colonic expression of GLP-1 in rats [69]. GLP-1 itself can inhibit the production of intestinal chylomicrons through the gut-brain axis [48]. CCK is a gastrointestinal hormone that induces gallbladder contraction [70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, supplementation with GOS has been indicated to stimulate the proliferation and/or activity of beneficial bacteria, especially Bifidobacteria and Lactobacillus ( Gopal et al, 2001 ; Monteagudo et al, 2016 ). In fact, research data have demonstrated that dietary supplementation of GOS in pregnancy sows can elevate the plasma immunoglobulin A to enhance the immune status ( Wu et al, 2021 ; Lee et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%